Midwifery Care with Frequent Urination on Pregnant Women at BPM Nuril Masrukah Candi Sidoarjo: Asuhan Kebidanan Dengan Sering Buang Air Kecil Pada Ibu Hamil Di BPM Nuril Masrukah Candi Sidoarjo - Okky Elvira Novianti; Evi Rinata; Rafhani Rosyidah (Academia Open, 2021)
Pregnancy is the fertilization or fusion of spermatozoa and ovum which is followed by bullying. Normal pregnancy lasts in 9 to 10 months. Complaints and discomfort can arise from the beginning of pregnancy to the end of pregnancy which can affect the physical and psychological condition of the mother. Pregnant women often complain in the third trimester and 96.7% experience complaints of frequent urination. The case study method used is observational (COC) Continuity of Care. From data collection and inspection there were no gaps and problem found, so no further special handling was needed.